2021
DOI: 10.3390/ijerph18199956
|View full text |Cite
|
Sign up to set email alerts
|

The Strengthening Mechanism of the Relationship between Social Work and Public Health under COVID-19 in China

Abstract: Social work and public health have always shared a common mission and vision in promoting human health. However, existing research tends to view social work and public health as two separate fields at both practice and policy levels, and these studies have largely neglected the consideration of how to integrate public health and social work. In the context of the COVID-19 epidemic, the link between the two has been strengthened and health social work has been given more importance. The question addressed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Encouraging these types of positive work environments could help reduce burnout, increase engagement, and improve task performance amongst employees (35). Given social workers play a vital role in improving health care services and reducing inequities for their clients, promoting work environments of social workers would have profound effects for promoting health service delivery and public health outcomes for the vulnerable Chinese clients' social workers serve (5,6,16). 82) recent study found individuals with higher emotional intelligence, tend to have lower rates of burnout because of their ability to better regulate inner emotions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Encouraging these types of positive work environments could help reduce burnout, increase engagement, and improve task performance amongst employees (35). Given social workers play a vital role in improving health care services and reducing inequities for their clients, promoting work environments of social workers would have profound effects for promoting health service delivery and public health outcomes for the vulnerable Chinese clients' social workers serve (5,6,16). 82) recent study found individuals with higher emotional intelligence, tend to have lower rates of burnout because of their ability to better regulate inner emotions.…”
Section: Discussionmentioning
confidence: 99%
“…First, the study illuminates the prevalence of high JD amongst Chinese social workers. Given high JD pose a significant risk of burnout, which has significant impacts on public health outcomes and health service delivery for their clients ( 5 , 6 , 16 ), Chinese social work agencies should initiate policies such as work-life balance policy to alleviate high workloads and provide support to make emotional workloads more manageable ( 69 71 ). These policies will not only reduce social worker burnout, but they also have the potential to increase public health outcomes and health service delivery of the clients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations